EVIDENCE OF CHEMICAL PATHWAYS OF HUMIFICATION: A STUDY OF AQUATIC HUMIC SUBSTANCES HEATED AT VARIOUS TEMPERATURES - Lu X.Q.; Hanna J.V.; Johnson W.D. (My University, 2001)
The effects of thermal evolution on the composition and structure of aquatic humic substances (HS) heated at temperatures from 100°C to 500°C in presence of helium were investigated using elemental analysis, FTIR and solid state 13C CP/MAS NMR spectroscopy, and Py-GC/MS spectrometry. Elemental composition results showed that with increasing heating temperatures, there was an increase in the atomic H/C ratio and a decrease in the atomic O/C ratio in the HS. FTIR, solid state 13C CP/MAS NMR, and Py-GC/MS results showed decreases in amounts of oxygen-containing groups followed by their subsequent disappearance at higher temperatures. Formation of aromatics was observed at expense of aliphatics at higher temperatures. This study has given a substantial amount of information on mass loss, structural evolution, and the degree of maturity as the humic substances are heated with increasing temperatures, suggesting that thermal evolution may play an important role in the contribution of the HS as a precursor of coal like organic materials.
Keywords: SWAMP HUMIC SUBSTANCES; ELEMENTAL COMPOSITION; ATOMIC RATIO; THERMAL EVOLUTION; MATURITY; FTIR; 13C CP/MAS NMR; PY-GC/MS